Factors Affecting the Participation of Sugarcane and Tobacco Farmers in Farmer Groups, Associations and Cooperatives in Indonesia - Rokhani, Rokhani; Fauziyah, Diana; Supriono, Agus; Hariyati, Yuli; Raharto, Sugeng; Hapsari, Triana Dewi; Adi, Ad Hariyanto; Khasan, Ahmad Fatikhul; Rondhi, Mohammad (Universitas Sebelas Maret, 2021)
The revitalization of farmer organizations has become the central paradigm in agricultural development. In Indonesia, increasing farmer participation in farmer groups, associations and cooperatives is the strategy to revitalize farmer organizations. This study aimed to determine the factors influencing farmers' participation in farmer groups, associations and cooperatives. This study employed data from the Sugarcane and Tobacco Plantation Farm Household Survey in 2014, consisting of 8,831 (70.73%) sugarcane farmers and 3,645 (29.27%) tobacco farmers. Logistic regression analysis was used to identify the factors contributing to farmers' participation in each organization. The results showed that harvest area, access to extension and contract farming positively affect farmers’ participation in organizations. Farmers' age and education positively affect their participation in associations and cooperatives but do not significantly affect their group participation. Land tenure has an ununiform effect on farmer participation in each organization. Tenant farmers are less likely to participate in farmer groups and cooperatives, but they tend to participate in associations. Meanwhile, the owner farmers are less likely to join cooperatives. Government support positively influences farmer group participation, shows a negative effect on participation in associations and has a non-significant effect on participation in cooperatives. Finally, farmers' wealth gives a positive effect on their participation in cooperatives, a negative effect on their participation in associations and a non-significant effect on farmer groups. These results depict that farmer groups are more inclusive than cooperatives and associations.